2021
DOI: 10.3390/ijerph182010646
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cyberbullying, Motivation and Learning Strategies, Academic Performance, and the Ability to Adapt to University

Abstract: Cyberbullying has become a frequent relational problem among young people, which has made it necessary to evaluate and prevent it in the university setting. The aim of this study is to examine the relationship between cyberbullying, motivation and learning strategies, the ability to adapt to university, and academic performance. A sample of 1368 Spanish university students (64% female) was administered a battery consisting of the European Bullying Intervention Project Questionnaire, the Learning and Study Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…According to the research of Aparisi et al [ 51 ], bullies, as well as bullies/victims, have greater difficulties in organizing and planning studies, in performing adequately in exams and develop fewer control and consolidation strategies than students who are neither bullies nor victims. In contrast, Clemmensen et al [ 52 ] show in their results that the difference between bullies, bullies/victims and the uninvolved were not significant but they were significant in the case of victims, who revealed lower scores than those who were classed as non-victim/non-bully.…”
Section: Discussionmentioning
confidence: 99%
“…According to the research of Aparisi et al [ 51 ], bullies, as well as bullies/victims, have greater difficulties in organizing and planning studies, in performing adequately in exams and develop fewer control and consolidation strategies than students who are neither bullies nor victims. In contrast, Clemmensen et al [ 52 ] show in their results that the difference between bullies, bullies/victims and the uninvolved were not significant but they were significant in the case of victims, who revealed lower scores than those who were classed as non-victim/non-bully.…”
Section: Discussionmentioning
confidence: 99%
“…They are more susceptible to developing depression in the future because of the considerable relationship between cyberbullying (victimization and interpretation) and depression (Zhang et al, 2020). Prior studies also show that university students who are the targets of cyberbullying experience anxiety, which has an impact on their academic performance (e.g., Aparisi et al, 2021). Additionally, other studies by Cenat et al (2019) revealed that the harm brought on by cyberbullying can negatively impact students' ability to interact in social and professional settings daily, result in the loss of vital support networks that promote emotional health, and make them more susceptible to selfdestructive behavior that causes anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of the present review is that, despite not restricting either the search or inclusion criteria according to age, studies conducted with over 18-year-olds were not identified. The examination of such a population, likely to include university students, would be of huge interest given that CB has also been highlighted to present a significant issue within this group [ 47 , 48 ]. This being said, this is not necessarily just a limitation of the present review but of the wider cyberbullying literature.…”
Section: Discussionmentioning
confidence: 99%